2020
DOI: 10.1039/d0tb01598a
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional iron MOF nanosheet as a highly efficient nanozyme for glucose biosensing

Abstract: Two-dimensional (2D) nanomaterials are attractive in catalysis due to their rich accessible active sites. Iron-based metal organic framework (MOF) is one of promising nanozymes because of its iron center and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(29 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Nowadays, various nanozymes have been served as catalytic labels for multi-category signal amplification in newly developed immunoassays. Numerous studies revealed that metal NPs (Au, Ag, Pt, Pd) [85,86], metal oxide NPs (Fe 3 O 4 , CeO 2 , MnO 2 , CuO) [87][88][89][90][91][92], carbon-based (graphene oxide, carbon nitride, carbon dots) [93][94][95][96], and MOFs-based nanomaterials [97][98][99] with peroxidase-, catalase-, oxidase-, superoxide dismutase-mimicking properties.…”
Section: Nanozyme For Signal Amplificationmentioning
confidence: 99%
“…Nowadays, various nanozymes have been served as catalytic labels for multi-category signal amplification in newly developed immunoassays. Numerous studies revealed that metal NPs (Au, Ag, Pt, Pd) [85,86], metal oxide NPs (Fe 3 O 4 , CeO 2 , MnO 2 , CuO) [87][88][89][90][91][92], carbon-based (graphene oxide, carbon nitride, carbon dots) [93][94][95][96], and MOFs-based nanomaterials [97][98][99] with peroxidase-, catalase-, oxidase-, superoxide dismutase-mimicking properties.…”
Section: Nanozyme For Signal Amplificationmentioning
confidence: 99%
“… Copyright 2022, ACS publications. Reproduced with permission [ 37 ]. Copyright 2020, RSC publications.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Addressing the limitations of natural enzymes such as low stability, high cost, and storage restrictions, nanozymes attracted a particular attention to enzymenanozymes biosensors elaboration. So, a plethora of peroxidase mimics, including metal-organic framework nanosheets, [13] nanoflowers, [14] nanodots, [15] and nanocages [16] etc., were coupled with oxidases for biosensing applications.…”
Section: Introductionmentioning
confidence: 99%